Families in the Shadow of Traumatic Experiences: Negative World Assumptions and Family Relationships. Issue 1 (21st October 2020) - Bachem, Rahel; Levin, Yafit; Stein, Jacob Y.; Solomon, Zahava
Abstract: World assumptions (WAs) are cognitive schemas concerning an individual's views of themselves, the world, and others. Although it is well established that WAs are negatively distorted by trauma exposure and strongly associated with posttraumatic psychopathology, the potential impact of WAs on close interpersonal relationships remains largely uninvestigated. The current study explored the implications of veterans' and their spouses' WAs on their marital and parental relationships. Male Israeli veterans ( N = 213) from the 1973 Yom Kippur War and their wives were assessed for WAs, marital adjustment, and positive parenting 35–37 years postwar. Analyses included actor–partner interdependence modeling with mediators (APIMem) and were conducted separately for the three domains of WAs: world benevolence, world meaningfulness, and self‐worth. The results indicated that both husbands' and wives' lower scores for all domain‐specific WA scales were associated with lower scores on measures of marital adjustment and positive parenting. Lower scores for both spouses on scales measuring world benevolence and self‐worth were associated with a spillover from lower marital adjustment to lower positive parenting. Finally, associations between one spouse's lower WA scores and the other spouse's spillover from lower marital adjustment to lower positive parenting (i.e., cross–spillover effects) were identified for wives' world benevolence ratings and husbands' self‐worth, d s = 0.14–0.72. These results point to the detrimental ramifications of negative WAs on family relationships and the dynamics between the marital and parental family subsystems. 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯: JOTS‐19‐0306.R3_Bachem_cantonese Traditional Chinese 創傷陰影下的家庭:負面的世界假設與家庭關係 摘要 : 世界假設(WAs)是關於個人對自己、世界以及他人看法的認知模式。儘管創傷暴露對世界假設產生了負面影響, 並與創傷後精神病理密切相關, 但世界假設對親密人際關係的潛在影響仍未得到充分研究。本研究探討了退伍軍人及其配偶的世界假設對其婚姻和父母關係的影響。 1973年贖罪日戰爭中的以色列男性退伍軍人(參與人數 = 213)和他們的妻子在戰後35‐37年進行了世界假設、婚姻調整和積極育兒評估。分析評估包括有調解人的行動者‐夥伴相互依賴模型(APIMem), 並對WA的三個領域分別進行了分析:世界仁慈、世界有意義以及自我價值。結果表明, 丈夫和妻子在所有特定領域的WA量表上的低分都與婚姻調整和積極養育措施的低分有關。夫妻雙方在衡量世界仁愛和自我價值的量表上的得分較低, 與從較低的婚姻調整到較低的積極父母育兒的溢出有關。最後, 配偶一方較低的WA分數與另一方從較低的婚姻調整到較低的積極養育的溢出之間的關聯(即交叉溢出效應)被確定為妻子的世界善意評級和丈夫的自我價值, 為ds=0.14‐0.72。以上結果表明, 消極的世界觀對家庭關係以及婚姻和父母家庭子系統之間的互動有不利的影響。 Simplified Chinese 创伤阴影下的家庭:负面的世界假设与家庭关系 摘要 : 世界假设(WAs)是关于个人对自己、世界以及他人看法的认知模式。尽管创伤暴露对世界假设产生了负面影响, 并与创伤后精神病理密切相关, 但世界假设对亲密人际关系的潜在影响仍未得到充分研究。本研究探讨了退伍军人及其配偶的世界假设对其婚姻和父母关系的影响。 1973年赎罪日战争中的以色列男性退伍军人(参与人数 = 213)和他们的妻子在战后35‐37年进行了世界假设、婚姻调整和积极育儿评估。分析评估包括有调解人的行动者‐伙伴相互依赖模型(APIMem), 并对WA的三个领域分别进行了分析:世界仁慈、世界有意义以及自我价值。结果表明, 丈夫和妻子在所有特定领域的WA量表上的低分都与婚姻调整和积极养育措施的低分有关。夫妻双方在衡量世界仁爱和自我价值的量表上的得分较低, 与从较低的婚姻调整到较低的积极父母育儿的溢出有关。最后, 配偶一方较低的WA分数与另一方从较低的婚姻调整到较低的积极养育的溢出之间的关联(即交叉溢出效应)被确定为妻子的世界善意评级和丈夫的自我价值, 为ds=0.14‐0.72。以上结果表明, 消极的世界观对家庭关系以及婚姻和父母家庭子系统之间的互动有不利的影响。